2020
DOI: 10.1007/s00068-020-01570-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure monitoring following traumatic brain injury: evaluation of indications, complications, and significance of follow-up imaging—an exploratory, retrospective study of consecutive patients at a level I trauma center

Abstract: Background Measurement of intracranial pressure (ICP) is an essential part of clinical management of severe traumatic brain injury (TBI). However, clinical utility and impact on clinical outcome of ICP monitoring remain controversial. Follow-up imaging using cranial computed tomography (CCT) is commonly performed in these patients. This retrospective cohort study reports on complication rates of ICP measurement in severe TBI patients, as well as on findings and clinical consequences of follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the generally accepted range for individuals in the supine position is 7.5 to 20 cmH 2 O in healthy adults [2]. In this investigation, the criteria for increased ICP (IICP) were delineated at 20 and 25 cmH 2 O, considering diverse reference values reported in previous studies [3,20,21].…”
Section: The Association Between Onsd and Iicpmentioning
confidence: 99%
“…However, the generally accepted range for individuals in the supine position is 7.5 to 20 cmH 2 O in healthy adults [2]. In this investigation, the criteria for increased ICP (IICP) were delineated at 20 and 25 cmH 2 O, considering diverse reference values reported in previous studies [3,20,21].…”
Section: The Association Between Onsd and Iicpmentioning
confidence: 99%
“…Furthermore, invasive intracranial pressure monitoring reduces the number of cranial CT scans performed on patients with increased intracranial pressure or those with a declining level of consciousness. This, in turn, lowers the number of patient evacuations and the hazards associated with transportation ( 18 ). A meta-analysis demonstrated that aggressive intracranial pressure monitoring and treatment resulted in a better prognosis for patients ( 19 ).…”
Section: Optimal Duration Of Invasive Intracranial Pressure Monitorin...mentioning
confidence: 99%